2012
DOI: 10.1007/s11739-012-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

ECG in patients with acute heart failure can predict in-hospital and long-term mortality

Abstract: Initial risk stratification in patients with acute heart failure (AHF) is poorly validated. Previous studies tended to evaluate the prognostic significance of only one or two selected ECG parameters. The aim of this study was to evaluate the impact of multiple ECG parameters on mortality in AHF. The Acute Heart Failure Database (AHEAD) registry collected data from 4,153 patients admitted for AHF to seven hospitals with Catheter Laboratory facilities. Clinical variables, heart rate, duration of QRS, QT and QTC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…11 This is supported by the findings of AHEAD (Acute Heart Failure Database) registry, which found that an increased QRS duration was independently associated with increased in-hospital mortality and long-term mortality. 13 This is also seen in data from the KorHF (Korean Heart Failure) registry, where the presence of both a widened QRS (>120 ms) and a prolonged PR interval (>200 ms) was independently associated with in-hospital death, post-discharge death and rehospitalization. 15 However, the THESUS-HF (the Sub-Saharan Africa Survey of Heart Failure) 12 cohort did not find any association between QRS width and 60-day or 180-day mortality.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…11 This is supported by the findings of AHEAD (Acute Heart Failure Database) registry, which found that an increased QRS duration was independently associated with increased in-hospital mortality and long-term mortality. 13 This is also seen in data from the KorHF (Korean Heart Failure) registry, where the presence of both a widened QRS (>120 ms) and a prolonged PR interval (>200 ms) was independently associated with in-hospital death, post-discharge death and rehospitalization. 15 However, the THESUS-HF (the Sub-Saharan Africa Survey of Heart Failure) 12 cohort did not find any association between QRS width and 60-day or 180-day mortality.…”
Section: Discussionmentioning
confidence: 65%
“…33 In the EHFS II (EuroHeart Failure Survey II) study, a statistically significant shorter QRS duration was observed among survivors at 1 year (100 ms IQR 82–120) compared with non‐survivors (110 ms IQR 90–130) . This is supported by the findings of AHEAD (Acute Heart Failure Database) registry, which found that an increased QRS duration was independently associated with increased in‐hospital mortality and long‐term mortality . This is also seen in data from the KorHF (Korean Heart Failure) registry, where the presence of both a widened QRS (>120 ms) and a prolonged PR interval (>200 ms) was independently associated with in‐hospital death, post‐discharge death and rehospitalization .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…arrhythmia) and suitable treatment can be planned. Abnormalities like QRS prolongation or junctional rhythm in the ECG obtained on admission have also prognostic importance and are associated with higher in-hospital and follow-up mortality (33). …”
Section: Clinical Evaluationmentioning
confidence: 99%